2011
DOI: 10.1109/taes.2011.5751238
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Waveform Design for High-Bit-Rate W-band Satellite Transmissions

Abstract: In the EHF (Extremely High Frequency) domain, W-band (75-110 GHz) offers promising perspectives for future satellite communications, mainly in terms of large bandwidth availability for high-bit-rate transmission. In this work 1 , an innovative physical (PHY) layer design for broadband satellite connections operating in W-band is proposed, which is based on the Prolate Spheroidal Wave Functions (PSWFs). PSWF waveforms (originally proposed in short-range indoor Ultra Wideband (UWB) communications) are aimed at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Unfiltered binary or quaternary modulations using rectangular pulse shaping (BPSK, QPSK), characterized by constant amplitude, are not acceptable for broadband transmission applications due to their high sidelobe power levels, not complying with the standard recommendation about spectrum usage. Frequency modulation schemes like Minimum Shift Keying (MSK) and Gaussian Minimum Shift Keying (GMSK) are resilient against nonlinear distortion and characterized by negligible sidelobe power level but, as shown in [6], are vulnerable to phase noise. We think that the effi- cient exploitation of EHF bandwidth portion will require a step-ahead in waveform design with respect to conventional state-of-the-art solutions.…”
Section: Ehf Satellite Link Impairmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfiltered binary or quaternary modulations using rectangular pulse shaping (BPSK, QPSK), characterized by constant amplitude, are not acceptable for broadband transmission applications due to their high sidelobe power levels, not complying with the standard recommendation about spectrum usage. Frequency modulation schemes like Minimum Shift Keying (MSK) and Gaussian Minimum Shift Keying (GMSK) are resilient against nonlinear distortion and characterized by negligible sidelobe power level but, as shown in [6], are vulnerable to phase noise. We think that the effi- cient exploitation of EHF bandwidth portion will require a step-ahead in waveform design with respect to conventional state-of-the-art solutions.…”
Section: Ehf Satellite Link Impairmentsmentioning
confidence: 99%
“…These waveforms, based on the solution of specific differential equations, are characterized by optimal energy concentration in time and frequency domain. In particular, PSWF of order 1 and order 2 can provide RF modulated signals characterized by a near-optimal compromise between spectral compactness (sidelobe power level 31.5 dB below the main lobe [6]) and envelope compactness (their Peakto-Average-Power-Ratio (PAPR) is 1 dB [6]). Therefore, the effect of nonlinear distortions can be drastically reduced, while maintaining a spectral efficiency rather similar to bandwidth-limited raised cosine waveforms.…”
Section: Impulse-based Uwb Waveformsmentioning
confidence: 99%
See 2 more Smart Citations
“…A M-ary PSM scheme based on the orthogonal properties of Hermite pulses is reported in Ghavami et al (2002), Wallace et al (2005) and de whereas such a scheme utilising PSWF is shown in Usuda et al (2004) to achieve high data rate in a severe multipath fading environment. A 4-ary PSM scheme based on PSWF acts as a physical layer for broadband satellite communications in W-band showing distinct advantages over raised cosine filtered quadrature amplitude modulation (QAM) (Sacchi et al, 2011). Performance comparison of UWB modulation schemes based upon the fifth derivative of Gaussian pulses is discussed in Abedi and Yagoub (2012).…”
Section: Introductionmentioning
confidence: 99%